Key technical solutions and standardization progress of high-speed optical modules - Bingbing WU; Wenyu ZHAO; Haiyi ZHANG (Dianxin kexue)
Optical modules are the basic building blocks of 5G transport networks, data center interconnections and all-optical access networks.With the rapid development of upper-layer service and applications, high-speed optical modules had become the key element to achieve high bandwidth and wide coverage in various application fields.Based on the basic concepts and the overall view of standardization research of optical modules, the technical solutions, standardization status and market development trend of 400 Gbit/s, 800 Gbit/s intensity and phase modulation high-speed optical modules were focused on.Finally, suggestions to promote the healthy development of optical modules in the future were proposed.